An Investigation of Abstract Construal on Impression Formation: A Multi-Lab Replication of McCarthy and Skowronski (2011). Issue 1 (10th May 2018) - McCarthy, Randy; Hartnett, Jessica; Heider, Jeremy; Scherer, Cory; Wood, Sarah; Nichols, Austin; Edlund, John; Walker, W.
Perceivers often view individuals described as "warm" to be generally positive and individuals described as "cold" to be generally negative. Consistent with the tenets of Construal Level Theory, McCarthy and Skowronski (2011 ) demonstrated this difference was larger among perceivers who were instructed the information was psychologically distant rather than psychologically near; however, those results have never been subjected to replication attempts. To test the replicability of those results, we closely replicated the methods of McCarthy and Skowronski (2011 ) Study 1b at eight separate data collection sites and pooled the results into a random-effects meta-analysis. Within the replication attempts, the overall effect was not significantly different from zero ( d = 0.10, 95% CI [–0.01, 0.22]) and an equivalence test confirmed this effect was smaller than our smallest effect size of interest. However, when the original study was incorporated into the meta-analysis, the overall effect was significantly different from zero in the theoretically-consistent direction ( d = 0.13, 95% CI [0.02, 0.24]). The weight of the overall evidence suggests the traits "warm" and "cold" are more influential among participants who were presented with information that was psychologically distant; however, this effect is small. Future research should try to identify more potent moderators, which would make the effect more affordable to detect.